Influence of Financial Literacy, Social Environment, and Financial Technology Against Financial Behavior - Simu, Tiberias Krisgaharu; Rahmawati, Christina Heti Tri; Yuniarto, Albertus Yudi (The Graduate School of Sahid University, 2023)
Students as the nation's successors have a role in increasing Indonesia's financial literacy index. Therefore, students need to be equipped with financial literacy, character building through the social environment so that they do not behave irrationally, use of financial technology (fintech) to facilitate financial transactions so that students can behave financially well by carrying out appropriate financial management. to determine the influence of financial literacy, social environment and fintech on the financial behavior. This research uses 875 students from the Faculty of Economics, Sanata Dharma University Class of 2019-2020. This research sample uses a portion 96 students. Purposive sampling was used as a sampling technique with the criteria being that respondents were fintech users, for example Gopay, Shoope-Pay, Ovo, Dana, and so on. Chi-Square and Multiple Linear Regression are used as data analysis techniques. The research results show that financial literacy, social environment and fintech the financial behavior of students at the Faculty of Economics, Sanata Dharma University. That it is hoped that students will have knowledge about financial literacy, be able to choose the right social environment, and have knowledge about fintech products that will help students have good behavior so they can carry out appropriate financial management and avoid illegal investments.